Monitoring kapasitas tabung gas berbasis Internet of things (iot) - Suwardoyo, Untung; fahriyanto, fery (Jurnal Sintaks Logika, 2022)
The problem that is most often experienced by housewives in the kitchen in preparing food is that they often forget about the availability of cooking utensils in the kitchen, in this case gas cylinders. This of course will cause the process of managing food in the kitchen to be hampered. This study uses a load cell weight sensor with a maximum capacity of 10 kg to be able to detect the weight of a gas cylinder which is then connected to an HX711 modulator which is useful for amplifying and analyzing the load cell weight sensor signal. The measurement results from the weight sensor are then processed by the ESP32 controller board to be processed and uploaded to the Firebase database in real time which can then be viewed on a smartphone application that is connected to the internet network. Based on the data from this study, it can be concluded that the application can display notifications for every 10% decrease in gas cylinder capacity and the comparison of the weight of the digital scale measurement results with the weight measured using the weight sensor still has an error with an average of 2.83%.